Photo‐Patterning of Non‐Fouling Polymers and Biomolecules on Paper. (9th April 2014) - Tischer, Thomas; Rodriguez‐Emmenegger, Cesar; Trouillet, Vanessa; Welle, Alexander; Schueler, Vincent; Mueller, Jan O.; Goldmann, Anja S.; Brynda, Eduard; Barner‐Kowollik, Christopher
<x xml:space="preserve">Abstract</x> Functional cellulose substrates with tetrazole moieties are generated to serve as universal platforms for the spatio‐temporal immobilization of synthetic ultra‐low fouling polymer brushes and protein species via a nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC)‐based protocol. Poly(carboxybetaine acrylamide) brushes are grafted from initiators photo‐patterned by NITEC utilizing single electron transfer living radical polymerization. Streptavidin is photo‐immobilized with remarkable efficiency, opening the possibility to generate new materials for biomedical and biosensing applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>